Associative learning is inversely related to reversal learning and varies with nestling corticosterone exposure - Bebus, Sara; Small, T.; Jones, B.; Elderbrock, E.; Schoech, S. (2016)
© 2015 The Association for the Study of Animal Behaviour. Intraspecies differences are fundamental to natural selection, yet individual differences in cognition in free-living populations have received little attention. Proactive and reactive coping styles describe individual differences in personality and related stress physiology; however, the coping style model can be extended to include predictions regarding measures of cognition. We compared two measures of personality (neophobia and exploratory behaviour) included in the coping style model to cognitive performance on colour-based associative and reversal learning tests in adult Florida scrub-jays, Aphelocoma coerulescens. Also, as exogenous glucocorticoid treatment can affect cognitive performance, we examined whether an individual's naturally occurring physiological phenotype, reflected by corticosterone measures obtained during development and at the time of the learning tests, covaried with learning performance. Performance on associative and reversal learning tests were inversely related. Scrub-jays with low levels of corticosterone as 11-day-old nestlings performed better on an associative learning test as adults, and there was a marginally nonsignificant trend for nestlings with high levels of corticosterone to perform better on a reversal learning test. There was also a marginally nonsignificant trend for neophobic birds to perform better on reversal learning tests. There were no relationships either between adult stress-induced corticosterone levels and learning, or between exploratory behaviour and learning. Our findings provide evidence that variation in sensitivity to environmental conditions, as reflected by an individual's coping style, underlie the specific strategy by which individuals perform cognitive tasks (i.e. cognitive style). Florida scrub-jays experience a trade-off in performance between types of learning that covary with early corticosterone exposure.